ANALISIS PENGEMBANGAN DESA HALIAU SEBAGAI OBJEK DAN DAYA TARIK WISATA - Indah Komala Sari; Abdi Fithria; Khairun Nisa (Universitas Lambung Mangkurat, 2021)
Theepurposeooffthisrstudypwasstooanalyzeethe development of the village of Haliau as an object and tourist attraction, in Batu Benawa sub-district, Hulu Sungai Tengah Regency, South Kalimantan. Sampling for interviews using the Slovin formula based on the number of family heads with an error tolerance of 10%. Haliau village has two attractions, Haluhang Haliau and Outbound Bunga Water Park and Water Park which need to be developed with the right strategy seen from the SWOT analysis (StrengthsmWeaknesseslOpportunities Threats) by evaluating using IFAS andoEFAS matrices by determining strategies based on position in the matrix awareness. The results of IFAS and EFAS show that the absolute number of strength and opportunity factor scores (S + O) = 1.80 + 1.85 = 3.65. The absolute number of strength and threat factor scores (S + T) = 1.80 + 1.65 = 3.45. The absolute number of weakness and threat scores (W + T) = 1.10 + 1.65 = 2.75. The absolute number of weaknesses and opportunities scores (W + O) = 1.10 + 1.85 = 2.95. The greatest value is found in the sum of strength and opportunity factors. Reduction value of internal factors strengths and weaknesses (S-W) = 1.80 + 1.10 = 2.90. The value of reduction from external factors of opportunity and threat (O-T) = 1.85 + 1.65 = 3.5. The sum of internal and external factor values shows that the internal value is 0.75 and the external value is 0.15 from that value, so the SO strategy is in quadrant I, so from this value the strategy chosen is an aggressive strategy. Aggressive strategy is a strategy that utilizes all the strengths to take advantage of the greatest opportunitiesTujuan penelitian ini yaitu analisis pengembangan desa Haliau sebagai objek dan daya tarik wisata, di KecamatanOBatuLBenawaLKabupatenOHulu SungaiPTengah, Kalimantan Selatan. Pengambilan sampel untuk wawancara menggunakan rumus slovin berdasarkan jumlah kepala keluarga dengan toleransi error 10 %. Desa Haliau mempunyai dua objek wisata yaitu Limbuhang Haliau dan Baruh Bunga Outbound dan WaterPark yang perlu dikembangkan dengan strategi yang tepat dilihat dari analisis SWOT (Strengths Weaknesses Opportunities Threats) dengan evaluasi menggunakan matriks EFAS dan IFAS dengan penentuan strategi berdasarkan posisi pada kuadran matriks. Hasil EFAS dan IFAS diketahui jumlah absolut skor faktor kekuatan dan peluang (S+O) = 1,80 + 1,85 = 3,65. Jumlah absolut skor dari faktor kekuatan danaancaman (S+T) = 1,80 + 1,65 = 3,45. Jumlah absolut skor kelemahan dan ancaman (W+T) =1,10 + 1,65 = 2,75. Jumlah absolut skor kelemahan dan peluang (W+O) = 1,10 + 1,85 = 2,95. Nilai terbesar ditemukan pada penjumlahan faktor kekuatan dan peluang. Nilai pengurangan dari faktor internal kekuatan dan kelemahan (S-W) = 1,80 + 1,10 = 2,90. Nilai pengurangan dari faktor eksternal peluang dan ancaman (O-T) = 1,85 + 1,65 = 3,5. Penjumlahan dari nilai faktor internal dan eksternal menunjukkan bahwa nilai internal 0,75 dan nilai eksternal 0,15 dari nilai tersebut maka strategi SO berada pada kuadran I, sehingga dari nilai ini strategi yang dipilih adalah strategi agresif. Strategi agresif adalah strategi yang memanfaatkan semua kekuatan untuk menggunakan besarnya peluang